Irreversible Investment and the Expected Capital Stock with Stationary Uncertainty. - Mash, R (1999)
The paper analyses irreversible investment under stationary uncertainty in a competitive sector. It is shown that while future uncertainty reduces the desired capital stock, over time the expected actual capital stock is higher under uncertainty with irreversibility.